Problem-Based Learning Model and the Concept Map Method at Public Vocational School Students: Motivation and Learning Outcomes - Misriana, Misriana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The study's goal is to get class X APAPL students at public vocational school 3 Berau more interested in learning and help them do better in the Basics of Aquaculture sub-material Types of Aquatic Commodities. The classroom action research method consists of two cycles. Each cycle consists of three stages, namely (a) planning, (b) action/observation, and (c) reflection. In cycles I and II, learning is carried out with the Problem-Based Learning model using the concept map method. This study utilizes both qualitative data from observation sheets and quantitative data from the final test of each cycle. The test results for the students' concept mapping skills were good; the scores went up from 78.77 in cycle I to 80.75 in cycle II. All students who studied scored 70 and above. So it is concluded that the problem-based learning model with the concept map method can improve the motivation and learning outcomes of class X students of public vocational school 3 Berau.